A Novel Interface for the Graphical Analysis of Music Practice Behaviors - Sokolovskis, Janis; Herremans, Dorien; Chew, Elaine (Frontiers in Psychology, 2018)
Practice is an essential part of music training, but critical content-based analyses of practice behaviours still lack tools for conveying informative representation of practice sessions. To bridge this gap, we present a novel visualisation system, the Music Practice Browser, for representing, identifying, and analysing music practice behaviours. The Music Practice Browser provides a graphical interface for reviewing recorded practice sessions, which allows musicians, teachers, and researchers to examine aspects and features of music practice behaviours. The system takes beat and practice segment information together with a musical score in XML format as input, and produces a number of different visualisations: Practice Session Work Maps give an overview of contiguous practice segments; Practice Segment Arcs make evident transitions and repeated segments; Practice Session Precision Maps facilitate the identifying of errors; Tempo-Loudness Evolution Graphs track expressive variations over the course of a practice session. We then test the new system on practice sessions of pianists of varying levels of expertise ranging from novice to expert. The practice patterns found include Drill-Correct, Drill-Smooth, Memorisation Strategy, Review and Explore, and Expressive Evolution. The analysis reveals practice patterns and behaviour differences between beginners and experts, such as a higher proportion of Drill-Smooth patterns in expert practice.